2014
DOI: 10.7812/tpp/13-098
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Eye Movement Desensitization and Reprocessing (EMDR) Therapy in Medicine: Addressing the Psychological and Physical Symptoms Stemming from Adverse Life Experiences

Abstract: EMDR therapy provides physicians and other clinicians with an efficient approach to address psychological and physiologic symptoms stemming from adverse life experiences. Clinicians should therefore evaluate patients for experiential contributors to clinical manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
173
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(180 citation statements)
references
References 64 publications
1
173
0
6
Order By: Relevance
“…In accordance with the extant literature of pain (Ray & Zbik, 2001;Rome & Rome, 2000), the AIP model prospects that particularly chronic pain is related to past traumatic experiences, which is assumed to be limbically augmented during the sensitization process (Shapiro, 2014). More importantly, in review of the literature strong evidence with respect to the utilization of EMDR in the treatment of chronic pain has been emerged (Bergmann, 1998;Grant, 1998;Grant & Threlfo, 2002;Schneider et al, 2007;Schneider, Hofmann, Rost, & Shapiro, 2008).…”
Section: Murat Boysanmentioning
confidence: 55%
See 2 more Smart Citations
“…In accordance with the extant literature of pain (Ray & Zbik, 2001;Rome & Rome, 2000), the AIP model prospects that particularly chronic pain is related to past traumatic experiences, which is assumed to be limbically augmented during the sensitization process (Shapiro, 2014). More importantly, in review of the literature strong evidence with respect to the utilization of EMDR in the treatment of chronic pain has been emerged (Bergmann, 1998;Grant, 1998;Grant & Threlfo, 2002;Schneider et al, 2007;Schneider, Hofmann, Rost, & Shapiro, 2008).…”
Section: Murat Boysanmentioning
confidence: 55%
“…The reported scores of EMDR treated patients with SSD on the SF-36 improved considerably in all domains. Enhanced therapeutic outcomes were also evident for highly reduced scores of somatization subscale of the SCL-90 R, depression and anxiety over 6 week course of the EMDR treatment that can be attributable to the validity of basic hypothesis of the AIP model as to the significant associations between emotions and somatic sensations on the basis of prior painful memories (Shapiro, 2001(Shapiro, , 2014. More importantly, in consonant with previous suggestions as to effectiveness of psychotherapy in the literature (Hauser et al, 2009;Henningsen et al, 2007;Wulsin, 2014) the greater effect sizes in EMDR alone treated group relative to duloxetine treatment which were indicative of incomparable improvement in outcome measures showed that EMDR therapy should be considered as one of the first-line treatment alternatives in SSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of EMDR on PTSD in adults has been demonstrated in various reviews and in a meta-analysis (Bisson, Roberts, Andrew, Cooper, & Lewis, 2013; Chen et al, 2014; Shapiro, 2014). Together with TF-CBT, EMDR is recommended as a first-choice treatment for PTSD in various international practice guidelines (National Institute for Health and Clinical Excellence, 2005; Ursano et al, 2004; van Balkom et al, 2013; World Health Organization, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Begitu pula dengan hasil temuan Korn (2009) yang menemukan bahwa EMDR lebih cepat memberikan efek dari pada exposure therapy dalam menangani trauma. Hal lain yang turut merangsang ide untuk mengulas EMDR sebagai penanganan PTSD adalah EMDR telah banyak dijadikan sebagai bahan penelitian di berbagai bidang, misalnya efektif dalam menurunkan kecemasan patologis pada penderita Generalized Anxiety Disorder (Farima, Dowlatabadi, & Behzadi, 2015), berguna dalam penanganan masalah gangguan obsesif-kompulsif (Böhm & Voderholzer, 2010), mampu menangani dan menurunkan depresi (Moghadam, Moghadam, & Salehian, 2015), mengurangi stres akademik (Henrikus, 2015), menurunkan kecemasan pada korban penganiayaan (Tarquinio et al, 2012), efisien bagi ahli klinis dalam mengakses simptom fisiologis dan psikologis yang mempengaruhi pengembangan kehidupan individu (Shapiro, 2014), mampu menurunkan trauma pada anak-anak (Rodenburg et al, 2009) serta mampu menurunkan simptom trauma secara signifikan (Sack, Lempa, & Lamprecht, 2007).…”
unclassified